Hemoglobin A1c to Determine the Prevalence of Undiagnosed Carbohydrate Intolerance in Pregnancy [13D]. (May 2020) - Dinglas, Cheryl; Cochrane, Elizabeth; Umesh, Vaibhavi; Bernasko, James
Abstract : INTRODUCTION: Our objective was to evaluate an antepartum diagnostic approach to differentiate between women who had pre-pregnancy carbohydrate intolerance (pre-diabetes or overt diabetes) versus those who had pre-pregnancy normal carbohydrate tolerance using hemoglobin A1c (HbA1c). METHODS: An IRB approved retrospective observational study was conducted with women who had HbA1c measured at the initiation of prenatal care between July 2015 and June 2016. Patients with known pre-pregnancy diabetes, or condition affecting HbA1c (ie, hemoglobinopathy) were excluded. The prevalence of undiagnosed overt diabetes (HbA1c>6.5%), pre-diabetes (HbA1c of 5.7- 6.4%) and normal carbohydrate tolerance (HbA1c⩽5.6%) was determined. Among those with HbA1c <6.5%, rates of "true gestational diabetes mellitus (GDM)" and their postpartum follow up testing results were evaluated. Maternal characteristics were also extracted. RESULTS: 205 women were included. 5 (2.4%) had HbA1c >6.5%, 38 (18.5%) had HbA1c between 5.7–6.4%, and 162 (79%) had HbA1c ⩽5.6%. Of the women with HbA1c <6.5%, 30 women (15%) were diagnosed with GDM based on IADSPG criteria. GDM was diagnosed in 18% of women with HbA1c between 5.7–6.4% and 14% of those who had HbA1c ⩽5.6%. Further, only 8 (26.7%) completed the recommended 4–12 weeks postpartum GTT. CONCLUSION: Antepartum HbA1c testing can help identify women who had carbohydrate intolerance before pregnancy. Early identification may capture a high risk population during prenatal care and enable appropriate antepartum management and timely referrals. Pre-delivery identification of pre-existing carbohydrate intolerance proves superior to post-delivery identification because of the persistently poor completion rates of the latter.